1999
DOI: 10.1159/000054503
|View full text |Cite
|
Sign up to set email alerts
|

Regional Serotonin Metabolism under Basal and Restraint Stress Conditions in the Brain of Transgenic Mice with Impaired Glucocorticoid Receptor Function

Abstract: Transgenic (TG) mice deficient in glucocorticoid receptors (GR) were used in order to study the effects of a reduced GR function on adrenocorticotropin hormone and corticosterone plasma levels and on serotonin metabolism in different brain areas under basal resting conditions, after a 30-min restraint stress and 60 min after the end of the restraint stress. There was no difference in basal or stress-induced levels of either adrenocorticotropin hormone or corticosterone in control and TG mice, but the return of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…These mice exhibit deficits in spatial learning, enhanced responses to novelty and decreased locomotion in familiar environments [6]. These mice also exhibit changes in mesolimbic dopaminergic [26] and raphehippocampal serotonergic neurotransmission [27,28], as well as disrupted hippocampal long-term potentiation [29]. In addition, they show differences in binding to 5-HT 1 and 5-HT 2 receptors in hippocampal areas containing both glucocorticoid and mineralocorticoid receptors [30].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%
“…These mice exhibit deficits in spatial learning, enhanced responses to novelty and decreased locomotion in familiar environments [6]. These mice also exhibit changes in mesolimbic dopaminergic [26] and raphehippocampal serotonergic neurotransmission [27,28], as well as disrupted hippocampal long-term potentiation [29]. In addition, they show differences in binding to 5-HT 1 and 5-HT 2 receptors in hippocampal areas containing both glucocorticoid and mineralocorticoid receptors [30].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%
“…In these transgenic mice, Farisse et al [19]have demonstrated, under basal conditions, that hippocampal concentrations of 5-HT are similar to those found in control (B6C/3F1) mice. The 5-HT metabolite 5-hydroxyindoleacetic acid (5-HIAA) as well as the turnover of 5-HT, estimated with the 5-HIAA/5-HT ratio, was lower in the hippocampus of transgenic animals [19].…”
Section: Discussionmentioning
confidence: 63%
“…The 5-HT metabolite 5-hydroxyindoleacetic acid (5-HIAA) as well as the turnover of 5-HT, estimated with the 5-HIAA/5-HT ratio, was lower in the hippocampus of transgenic animals [19]. However, no difference in 5-HT and 5-HIAA levels or their ratio was found in the cortex, striatum or hypothalamus of transgenic compared to control mice [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations